2010
DOI: 10.1017/s1751731110001126
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid is important for the maintenance of maternal responsiveness and the establishment of maternal selectivity in sheep

Abstract: Amniotic fluid (AF) is important for the establishment of maternal behaviour in inexperienced ewes, but its role in experienced mothers remains to be studied. Here, the maintenance of post-partum maternal responsiveness and the establishment of exclusive bonding was investigated in multiparous ewes when AF was removed from the neonate or/and physical contact with the young was precluded for the first 4 h post partum. Maintenance of maternal responsiveness and establishment of exclusive bonding were measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…It is known that amniotic fluids are crucial for the establishment of a bond between a mother and her newborn. This fluid carries some chemosensory information that facilitates exclusive bonding (19). At this point, sniffing and licking behaviours come into play.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that amniotic fluids are crucial for the establishment of a bond between a mother and her newborn. This fluid carries some chemosensory information that facilitates exclusive bonding (19). At this point, sniffing and licking behaviours come into play.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of maternal behavior between Romanov, Ile de France, and Préalpes du Sud ewes and their lambs within 3 hours after birth, Poindron et al (1984b) found no major differences in multiparous dams. In contrast, primiparous Romanov ewes showed lower problems for lamb licking and less aggressive behavior to newborns compared with the other 2 breeds.…”
Section: Introductionmentioning
confidence: 86%
“…Most studies of Romanov ewes have been based on productivity, and only 2 reports were found supporting the assumptions of high maternal ability (Poindron et al, 1984b;Ricordeau et al, 1976). In a comparison of maternal behavior between Romanov, Ile de France, and Préalpes du Sud ewes and their lambs within 3 hours after birth, Poindron et al (1984b) found no major differences in multiparous dams.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Likewise, a mother may accept an alien lamb within four hours of giving birth if the young animal is impregnated with amniotic fluid. Interestingly, this suggests that the source of the amniotic fluid (i.e., whether it comes from the biological mother or another ewe) is not important, and that what truly matters is that the amniotic fluid contains attractive chemical cues that serve to facilitate individual recognition of the lamb (Poindron et al 1980;Levy et al 1983;Poindron et al 1984;Arteaga-Castaneda et al 2007;Poindron et al 2010). Keller et al (2003) have demonstrated that the presence of individual olfactory cues in amniotic fluids may also explain why about 30% of mothers display maternal selectivity from the very moment at which the foetus is expelled.…”
Section: Mutual Mother-young Olfactory Recognitionmentioning
confidence: 99%